Comparative study between S-(+)-ketamine–midazolam and fentanyl–droperidol in black-tufted marmosets (Callithrix penicillata) - Lopes, Luiz Fernando Larangeira; Gris, Vanessa Nadine; Ferraro, Mario Antonio; Cortopassi, Silvia Renata Gaido (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Sedative and antinociceptive effects of two anesthetic protocols in black-tufted marmosets were compared in this study. Twenty-six marmosets underwent chemical immobilization for physical examination, blood sampling, tattooing, and microchipping. Animals were randomly treated with S-(+)-ketamine (10 mg/kg) and midazolam (1 mg/kg) (KM) or fentanyl (12.5 µg/kg) and droperidol (625 µg/kg) (FD) given by intramuscular injection. Heart and respiratory rates were recorded. Sedation, antinociception, muscle relaxation, posture, auditory, and visual responses were evaluated using a scoring system. Sedation in KM was achieved faster (p < 0.001) and lasted for a shorter period of time (p = 0.0009). KM was similar to FD in its cardiorespiratory effects, auditory and visual responses. Both protocols promoted adequate sedation to allow manipulation. Animals in KM assumed lateral recumbency while animals in FD maintained a quadrupedal posture during evaluation. FD produced less intense sedation and muscle relaxation but a higher degree of antinociception compared to KM and is suitable for procedures that require analgesia in black-tufted marmosets.